2018
DOI: 10.1111/wvn.12319
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Mindfulness‐Based Stress Reduction Program on Blood Pressure: A Systematic Review of Literature

Abstract: The MBSR program is a promising behavioral complementary therapy to help people with hypertension lower their blood pressure through modifications in their lifestyle. More research is needed not only to identify the effectiveness of the MBSR program on blood pressure, but also to explore the mechanisms by which the program influences blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
1
23
0
7
Order By: Relevance
“…Lifestyle modifications should include the following (Table 8). [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Seasonal BP Variation 65 BP exhibits seasonal variation with lower levels at higher temperatures and higher at lower temperatures. Similar changes occur in people traveling from places with cold to hot temperature, or the reverse.…”
Section: Section 8: Treatment Of Hypertension 81 Lifestyle Modificatmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle modifications should include the following (Table 8). [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Seasonal BP Variation 65 BP exhibits seasonal variation with lower levels at higher temperatures and higher at lower temperatures. Similar changes occur in people traveling from places with cold to hot temperature, or the reverse.…”
Section: Section 8: Treatment Of Hypertension 81 Lifestyle Modificatmentioning
confidence: 99%
“…59 Although more research is needed to determine the effects of chronic stress on blood pressure, randomized clinical trials examining the effects of transcendental meditation/mindfulness on blood pressure suggest that this practice lowers blood pressure. 60 Stress should be reduced and mindfulness or meditation introduced into the daily routine.…”
Section: Reduce Stress and Induce Mindfulnessmentioning
confidence: 99%
“…[11] A 2018 systematic review suggested similar findings. [12] Customization of mindfulness interventions for specific patient populations has evidence to be effective, as a recent systematic review and meta-analyses demonstrated for Mindfulness-Based Cognitive Therapy effects on preventing depression relapse. [13] Consequently, we hypothesized that a mindfulness-based program adapted to those with elevated blood pressure, that trains participants in mindfulness skills of attention control, self-awareness and emotion regulation as well as the application of those skills in relation to modifiable determinants of blood pressure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus stress and anxiety may be better controlled. Secondly, mindfulness has been shown to promote body awareness, relaxation and cognitive coping processes that are associated with parasympathetic activation, that have been shown to reduce BP [34]. From this review it appears that effective interventions can be delivered individually or in groups and can help enhance wellbeing [34].…”
Section: Discussionmentioning
confidence: 97%